Views of traditionaly circumcised Xhosa men towards medical male circumcision - Dingindlela, Lindithemba (My University, 2015)
South Africa is characterised by high rate of complications and deaths associated with traditional male circumcision, and even though young initiates die in circumcision schools during circumcision seasons, thousands of young boys still want to get circumcised. The purpose of this research is to look at views of traditionally circumcised Xhosa men towards medical male circumcision and to get views of these traditional circumcising communities on how medical male circumcision could be done without losing traditional values of the practice. A qualitative research method was used to undertake this research. The sampling method use was non probability – purposive sampling. Literature relevant to the study is reviewed and used and also interviews conducted to traditional circumcised men from Menjini Village, in the Eastern Cape. The major findings of the study are that traditionally circumcising men will not accept medical male circumcision in its current form, it was found that there has been no deaths that are known and reported that are associated with medical male circumcision. Traditional male circumcision is more than just the cutting of the foreskin, the ritual carries multiple of meanings and dimensions that are interconnected, these include, religious, spiritual, social, biomedical, aesthetic and cultural, all these need to be taken into account when dealing with male circumcision in South Africa. Another major finding is that the legislation introduced by government was not properly communicated to the affected communities and communities and open to a method that creates synergy between traditional and medical male circumcision, this method must also be compliant with the provisions of the legislation.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2014.